2013
DOI: 10.5152/jtgga.2013.00378
|View full text |Cite
|
Sign up to set email alerts
|

Is transabdominal ultrasound scanning of cervical measurement in mid-trimester pregnancy a useful alternative to transvaginal ultrasound scan?

Abstract: Objective: The aim of this study is to assess the correlation between transabdominal and transvaginal ultrasound measurements of the cervix in pregnancy. If transabdominal ultrasound measurement of cervical length is found to provide effective information, it could be used in patient counselling and when making clinical decisions. Material and Methods:One hundred and twenty seven pregnant patients between 18-26 weeks of pregnancy were enrolled in this prospective study for measuring cervical length, both by tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 13 publications
(11 reference statements)
0
14
0
Order By: Relevance
“…It has been reported that using a TACL with a >35‐mm cutoff would result in up to 40% of women avoiding TVU 19 . In our cohort, 89% of women did not require a TVCL using the same cutoff, which may benefit women of those cultures with a high number of women who decline TVU 22 . Informed consent is required to conduct all ultrasound examinations 23 .…”
Section: Educationmentioning
confidence: 74%
“…It has been reported that using a TACL with a >35‐mm cutoff would result in up to 40% of women avoiding TVU 19 . In our cohort, 89% of women did not require a TVCL using the same cutoff, which may benefit women of those cultures with a high number of women who decline TVU 22 . Informed consent is required to conduct all ultrasound examinations 23 .…”
Section: Educationmentioning
confidence: 74%
“…[37,38] Bladder fullness also can impact transabdominal CL. [39] In some studies, when measuring CL, transabdominal measurement does not reflect the transvaginal measurement accurately. [40,41] Thus, when assessing cervical stiffness, the cervix condition may be affected by the compression of bladder fullness.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have suggested that an empty bladder prohibits visualization of the cervix on TA ultrasound or that a full bladder falsely elongates the cervix. 16,17 We did not find a significant difference in the test characteristics of TA ultrasound to detect short cervix based on the deepest vertical pocket of urine in the bladder. However, it is important to consider that our study included only patients in whom a TA cervical length could be measured.…”
Section: Discussionmentioning
confidence: 61%